THE MAIN REASONS OF THE LOW EFFICIENCY OF OBTAINING ALUMINUM-RESISTANT REGENERANTS OF CEREAL CROPS - E. M. Lisitsyn (Вавиловский журнал генетики и селекции)
The mechanisms of aluminum resistance, acting at the cellular level, provide an opportunity of obtaining resistant forms of plants by the cell culture method. In practice, however, this approach has not become widely used because of difficulties of plant regeneration from callus culture. This article focuses the attention of readers on other causes of low efficiency of the approach. They include high intraspecific heterogeneity of cereal crops with regard to aluminum resistance; conventionality of the division of genotypes into resistant and sensitive, accepted in practice; appearance of acid- and aluminum-resistant regenerants not only under stress but also under control conditions without any action of the stress factor under study; lack of appropriate methods, connected to the specific behavior of aluminum in various media, when incorrectly chosen medium composition or рН conceal the action of aluminum. As a result of joint action of all reasons mentioned in the article, the offered techniques of creation of high-resistant regenerants of cereal crops are behind traditional methods of intravarietal selection in duration, labor consumption, cost, and efficiency.